Modeling and Experiments of Energy Storage in a Fluidized Bed with PCM. (2015) - Izquierdo-Barrientos, M.A.; Sobrino, C.; Almendros-Ibáñez, J.A.
Abstract: Over the last years, the development of PCMs has opened new ways to increase the storage capacity and the energy stored due to the high latent heat and high storage density of these materials. The aim of this work is to model the charging process of a fluidized bed with PCM material operating as an energy storage device. The temperature in the bed during the charging process of the fluidized bed has been modeled using the two-phase theory of fluidization. The dense phase is taken to be perfectly mixed and the bubble phase is taken to be in plug flow. The numerical model presented takes into account the fact that the phase change process of the bed material occurs over a temperature range. The energy equation of the dense phase is numerically solved in enthalpy form considering the dependence of enthalpy on temperature for phase change occurring over a range of temperatures. The model validity is verified against experimental data for two granular materials: sand, a typical material used in fluidized beds, and a granular phase change material with a mean particle diameter of 0.54 mm and a phase change temperature around 50 °C. For both materials the temperature profiles obtained numerically agree with the ones measured experimentally.